Forms of partnership in public administration reform for economic transformation in Indonesia - Atmosudirdjo, Prajudi (1997)
Public administration reform is, and in my opinion will always remain even in advanced industrialized countries, a very important national concern. Public administration reform in Indonesia is an integral part of the overall national development program. Each of the six cabinets formed these past 30 years has included a special member called `MENPAN' who is some kind of `minister for administrative reform'. The MENPAN is charged with the mission to look continuously for ways and means to improve the efficacy of public administration for national development and economic transformation
Keywords: Administrative reform - Indonesia; Administrative reform